Studi Manajemen Perkawinan Ternak Dengan Teknik Inseminasi Buatan (IB) Pada Sapi Madura Di UPT Pembibitan dan Kesehatan Hewan - Argus Argus; Irawati Suhra (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Artificial Insemination (AI) is a mating process, by unnaturally bringing sperm and egg cells together in female livestock (poultry and ruminants) with the help of human hands. The success of the AI technique is influenced by three main factors namely; livestock, cement and humans. UPT Livestock Breeding and Animal Health of Madura is one of the institutions for preserving Madura cattle germplasm, which further optimizes the AI program. The aim is to find out the factors that influence the success of Artificial Insemination, the process of detecting lust (estrus) and Artificial Insemination techniques. The method used in this study was direct observation using the artificial insemination method, namely rectovaginal. AI is an attempt to insert semen into the reproductive tract of female livestock using artificial tools and with human assistance or in other words marriages that are not carried out naturally. Detection of lust (Estrus) is the observation of signs of heat in a cow to be inseminated, detection of heat is an important factor in the process of artificial insemination because it determines the time for proper and successful mating. The AI technique in cattle is the rectovaginal method, in which the hand is inserted into the rectum and then holds the part of the cervix that is most easily identified because it has a hard anatomy, then the insemination gun is inserted through the vulva, into the vagina up to the cervix.